2003
DOI: 10.1038/nmat902
|View full text |Cite
|
Sign up to set email alerts
|

Controlled growth of tetrapod-branched inorganic nanocrystals

Abstract: Nanoscale materials are currently being exploited as active components in a wide range of technological applications in various fields, such as composite materials, chemical sensing, biomedicine, optoelectronics and nanoelectronics. Colloidal nanocrystals are promising candidates in these fields, due to their ease of fabrication and processibility. Even more applications and new functional materials might emerge if nanocrystals could be synthesized in shapes of higher complexity than the ones produced by curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
1,392
1
22

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 1,412 publications
(1,459 citation statements)
references
References 32 publications
44
1,392
1
22
Order By: Relevance
“…Moreover, the nucleation stage can yield nuclei with unstable structure inducing phase transitions during nanoparticle growth [8]. For example, the synthesis of nano-tetrapods is based on a delicate balance between stabilities of cubic and hexagonal phases in certain II-VI materials [8,9].…”
mentioning
confidence: 99%
“…Moreover, the nucleation stage can yield nuclei with unstable structure inducing phase transitions during nanoparticle growth [8]. For example, the synthesis of nano-tetrapods is based on a delicate balance between stabilities of cubic and hexagonal phases in certain II-VI materials [8,9].…”
mentioning
confidence: 99%
“…Scientist gained significant control both the over size [7] and surfaces [8][9][10][11][12] for nanoparticles. They have demonstrated that anisotropy in nanostructure like triangular prisms [13][14][15][16][17][18], nanoscale rods [19][20][21][22][23][24][25][26], nanoshells [27][28][29][30][31], multipods [32][33][34], disks [35][36][37][38][39] and cubes [40][41][42] shows better performance over solid spheres. …”
Section: Nanomaterials and Nanotechnologymentioning
confidence: 99%
“…In general, there are several methods like solution cast technique, vapor phase approach, vapor liquid growth, co-precipitation method, sol-gel method , solution phase growth based on capping agents are used for the synthesis of nano-particles [2][3][4][5] . In recent scenario, tremendous effort has been done towards inorganic materials for the synthesis of nanoparticles towards a step into semiconductors due to its precise control and their size 6 , shape 7 , composition, crystal structures, strongly electronic charge carriers and also optical properties 8 . An attempt has been made to synthesize CdS and CdTe nanocrystals due to their semiconducting behavior and their unique properties 9,10 .…”
Section: Introductionmentioning
confidence: 99%